A Communications Strategy of the Malaysian Research Universities to add Value - Man, Nurafiq Inani; Abdullah, Assoc. Prof. Dr. Zulhamri; Tamam, Ezhar; Hasan, Nurul Ain (Jurnal The Messenger, 2019)
This paper s purpose is to understand what criteria constitutes narratives in the vision and mission statements on the corporate website of the Malaysian research universities based on storytelling elements. By looking at the vision and mission statements, through qualitative content analysis to discover what type of storytelling use in the local research university and to examine if it helps to add value and effectively use as corporate strategy practice to better position itself among the top 100 world-class university . The results of this study, provide a preliminary findings of higher education institutions practice of their narratives in order to gain a competitive advantage within education industry. The paper also be valuable and provide an insight on how universities in Malaysia to communicate their narratives and corporate strategy in order to gain a competitive advantage and position to be the world-class university .